2021
DOI: 10.15345/iojes.2021.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Argumentation-Supported PBL on the Determination of PreService Science Teachers' Misconceptions about the Particulate, Space, and Motion Nature of Matter

Abstract: Within the scope of the study, the effect of the argumentation-supported problem based learning method on the detection of the misconceptions of the students studying in the Department of Science Education about "Particulate, Space and Motion Nature of Matter" was examined. Based on this main purpose action research in practice-based was applied in the study, one of the qualitative research methods. The study group of the research consists of 22 pre-service science teachers. It was observed that pre-service sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…In a study examining students' misconceptions about the "Particulate, Space, and Motion Nature of Matter", it was observed that students were busy with more unscientific claims before the AS-PBL application and they could not use their supporting and rebuttal skills adequately. As the students repeated and experienced the activities in the practices frequently, it was determined that most of them had targeted arguments and were able to use both their justification and rebuttal skills more frequently (Okur & Güngör Seyhan, 2021). In another study on the use of argumentation-supported problem-based learning (AS-PBL) in pre-service science teachers' learning on the topic of "colligative properties", it was observed that preservice science teachers had misconceptions about chemistry; They were able to present only one conclusion sentence for the questions asked about the subject before the application.…”
Section: Related Researchmentioning
confidence: 99%
See 4 more Smart Citations
“…In a study examining students' misconceptions about the "Particulate, Space, and Motion Nature of Matter", it was observed that students were busy with more unscientific claims before the AS-PBL application and they could not use their supporting and rebuttal skills adequately. As the students repeated and experienced the activities in the practices frequently, it was determined that most of them had targeted arguments and were able to use both their justification and rebuttal skills more frequently (Okur & Güngör Seyhan, 2021). In another study on the use of argumentation-supported problem-based learning (AS-PBL) in pre-service science teachers' learning on the topic of "colligative properties", it was observed that preservice science teachers had misconceptions about chemistry; They were able to present only one conclusion sentence for the questions asked about the subject before the application.…”
Section: Related Researchmentioning
confidence: 99%
“…It is emphasized that in problem-based learning, it may be advantageous to integrate argumentation-supported applications, especially in the discussion stage, to compensate for the lack of knowledge acquisition in students (Kelly & Finlayson, 2009;Nussbaum & Edwards, 2011). As a result, argumentation-supported PBL has an important role in science teacher education and research revealed that these applications will increase students' science academic achievements and in eliminating misconceptions about chemistry in students (Okur & Güngör Seyhan 2021).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 3 more Smart Citations